Calidad del suelo con indicador carbono/nitrógeno en plantaciones de Cedrelinga cateniformis (Ducke) Ducke”, de diferentes edades en Puerto Almendra, Loreto-Perú, 2023 - Valles Pezo, Luz Gabriela (2025)
Soil quality, assessed using the carbon/nitrogen (C/N) indicator in Cedrelinga cateniformis (Ducke) Ducke plantations, is essential for understanding nutrient dynamics and the health of the forest ecosystem, as this indicator reflects the balance between organic matter processing and nitrogen availability for plants. This study, conducted at the Puerto Almendra Forestry Research and Teaching Center, analyzed soil quality in Cedrelinga cateniformis plantations of different ages using the Walkley & Black method to determine organic matter. The results show that, in 2023, organic matter in the soil's organic layer will be medium, while in the mineral layer it will be low. The carbon content in the organic layer is classified as moderate (1-3%), and in the mineral layer it is less than 1%. Likewise, total nitrogen in the organic layer is medium, while in the mineral layer it is very low. However, significant improvements are evident from the plantations' age of 43 years onward, reaching levels considered good in the organic layer, comparable to those of a natural forest. Finally, the soil C/N ratio is in a balanced range between 11.56 and 12, suggesting an adequate biological and chemical balance, reflecting good soil quality in these plantations.